Keanekaragaman Jenis Capung (Ordo Odonata) Pada Berbagai Tipe Habitat Di Kecamatan Leuwiliang Kabupaten Bogor - Raja Rhamdany Harahap; Insan Kurnia; Gatot Widodo (Program Studi Pendidikan Biologi, FKIP Universitas Kuningan, 2022)
Dragonflies and damselflies (Odonata) are insects with an important role for biological control and environmental quality indicators. Odonata are scattered in various types of habitats, especially those associated with freshwater ecosystems. The aim of this research is to study the diversity of odonata in various habitat types in Leuwiliang District, Bogor Regency. The study was conducted on 10 habitat types with a total of 1289 observation lines. In total found 23 species of odonatan from eight families and two sub-orders. The highest species richness was found in stream water habitats (22 species) and the lowest in field habitats (five species). The chi-square test for the number of species and the number of individuals differed significantly between habitat types. The species diversity index ranged from 1.23-2.24 and the similarity index ranged from 0.39-0.71. The highest community similarity index was between lakes habitats and field habitats. The results of the MDS analysis resulted in three groups of odonata communities according to their habitat type.